PENGARUH KEPEMILIKAN INSTITUSIONAL, UKURAN PERUSAHAAN, PROFITABILITAS DAN RISIKO BISNIS TERHADAP KEBIJAKAN HUTANG PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2008-2012 - Umi Mardiyati; Susi Susanti; Gatot Nazir Ahmad (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2014)
The  purpose  of  this  study  is  to  know  the  effect  of Institutional Ownership, Firm Size, Profitability, and Business Risk on Manufacture Firm Debt Policy Listed in Indonesia Stock Exchange. The sample using purposive sampling. The research model in this study  employs  panel data analysis with fixed effect approach. The empirical results  show that institutional ownership and firm size have  positive  and  significant  effect  on debt policy. ROA have negative  significant  effect  on debt policy, but business risk have  negative  and not significant effecton debt policy. Simultaneous test showed that institutional ownership, firm size, profitability, and business risk effect the debt policy.Key words:  Institutional Ownership, Firm Size, ROA, Business Risk, Debt Policy, Manufacture Firm